Acute Lymphoblastic Leukemia in a 10-Year-Old Boy With Cystic Fibrosis – Improvement of Pulmonary Function During Chemotherapy in spite of Intermittent Pseudomonas Aeruginosa Colonisation - Dopfer, C.; Kentouche, K.; Gruhn, B.; Dopfer, R.; Becker, S.; Mentzel, H.-J.; Beck, J. F.; Mainz, J. G. (Klinische Pädiatrie, 2011)
Multiorgan involvement in cystic fibrosis (CF), including chronic airway infection with pathogens like Pseudomonas aeruginosa, is a critical risk factor in patients with malignancy during aggressive immunosuppressive therapy, and was therefore formerly associated with high mortality rates. A 10 year old boy with CF and acute lymphoblastic leukemia (ALL) underwent induction and reinduction treatment without severe infectious complications whereas lung function improved.
Keywords: cystic fibrosis; leukemia; pulmonary function; osteopenia; cerebral venous thrombosis; liver toxicity